2006
DOI: 10.1016/j.canlet.2005.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotection by sulforaphane: Keep one eye beyond Keap1

Abstract: Sulforaphane (SFN) is an isothiocyanate found in cruciferous vegetables, with particularly high levels detected in broccoli and broccoli sprouts. Over a decade ago, this phytochemical was identified as a likely chemopreventive agent based on its ability to induce Phase 2 detoxification enzymes, as well as to inhibit Phase 1 enzymes involved in carcinogen activation. Considerable attention has focused on SFN as a 'blocking' agent, with the ability to modulate the Nrf2/Keap1 pathway, but recent evidence suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(114 citation statements)
references
References 48 publications
2
109
1
2
Order By: Relevance
“…Therefore it is coming up as an economical, easily available, and novel approach to cancer treatment and management (Karikas, 2010). Sulforaphane is an isothiocyanate, found in cruciferous vegetables, such as broccoli, kale, and cauliflower displays significant chemopreventive activity resulting from its inhibition of carcinogen-activating enzymes and induction of detoxification enzymes affecting carcinogen metabolism and disposition and by modulating epigenetic machinery (Barcelo et al, 1996;Basten et al, 2002;Myzak et al, 2006;Gibbs et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is coming up as an economical, easily available, and novel approach to cancer treatment and management (Karikas, 2010). Sulforaphane is an isothiocyanate, found in cruciferous vegetables, such as broccoli, kale, and cauliflower displays significant chemopreventive activity resulting from its inhibition of carcinogen-activating enzymes and induction of detoxification enzymes affecting carcinogen metabolism and disposition and by modulating epigenetic machinery (Barcelo et al, 1996;Basten et al, 2002;Myzak et al, 2006;Gibbs et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies show that the inhibition of clonogenicity was observed with much lower doses than for the inhibition of Akt. It is therefore possible that Aktindependent prosurvival pathways, such as extracellular signal-regulated kinase/c-Jun-NH 2 -kinase/p38 may be responsible for inhibition in the clonogenic ability and long-term survival of ovarian cancer cells, which needs investigation (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It activates Nrf2, possibly by modifying the sensor cysteines present in Keap1 [27,28]. While considerable attention has focussed on sulforaphane as a ''blocking'' agent, with the ability to modulate Nrf2-Keap1 signaling, it also exerts anti-inflammatory effects [29]. Thus, sulforaphane inhibited lipopolysaccharideinduced activation of NF-jB and COX-2 expression in cultured mouse macrophages [30].…”
Section: Chemopreventive Phytochemicals Targeting Nf-jb and Nrf2mentioning
confidence: 99%